Polypharmacy and Risk of Antiretroviral Drug Interactions Among the Aging HIV-Infected Population - Holtzman, Carol (Springer US, 2013)
BACKGROUND: Among aging HIV-infected adults, polypharmacy and its consequences have not been well-described. OBJECTIVE: To characterize the extent of polypharmacy and the risk of antiretroviral (ARV) drug interactions among persons of different ages. DESIGN AND PARTICIPANTS: Cross-sectional analysis among patients within the HIV Outpatient Study (HOPS) cohort who were prescribed ARVs during 2006–2010. MAIN MEASURES: We used the University of Liverpool HIV drug interactions database to identify ARV/non-ARV interactions with potential for clinical significance. KEY RESULTS: Of 3,810 patients analyzed (median age 46 years, 34 % ≥ 50 years old) at midpoint of observation, 1,494 (39 %) patients were prescribed ≥ 5 non-ARV medications: 706 (54 %) of 1,312 patients ≥ 50 years old compared with 788 (32 %) of 2,498 patients < 50 years. During the five-year period, the number of patients who were prescribed at least one ARV/non-ARV combination that was contraindicated or had moderate or high evidence of interaction was 267 (7 %) and 1,267 (33 %), respectively. Variables independently associated with having been prescribed a contraindicated ARV/non-ARV combination included older age (adjusted odds ratio [aOR] per 10 years of age 1.17, 95 % CI 1.01–1.35), anxiety (aOR 1.78, 95 % CI 1.32–2.40), dyslipidemia (aOR 1.96, 95 % CI 1.28–2.99), higher daily non-ARV medication burden (aOR 1.13, 95 % CI 1.10–1.17), and having been prescribed a protease inhibitor (aOR 2.10, 95 % CI 1.59–2.76). Compared with patients < 50 years, older patients were more likely to have been prescribed an ARV/non-ARV combination that was contraindicated (unadjusted OR 1.44, 95 % CI 1.14–1.82), or had moderate or high evidence of interaction (unadjusted OR 1.29, 95 % CI 1.15–1.44). CONCLUSIONS: A substantial percentage of patients were prescribed at least one ARV/non-ARV combination that was contraindicated or had potential for a clinically significant interaction. As HIV-infected patients age and experience multiple comorbidities, systematic reviews of current medications by providers may reduce risk of such exposures.